Antecedents of approach-avoidance goals in sport - Morris, R. L.; Kavussanu, M. (Journal of Sports Sciences, 2008)
We investigated antecedents of mastery-approach, mastery-avoidance, performance-approach, and performance-avoidance goals in sport. University athletes (n = 230) aged 18 - 25 years (mean 20.3 years, s = 1.5) completed measures of approach-avoidance goals, perceived parental motivational climate, perceived team motivational climate, perceived competence, and demographics. Multiple regression analyses revealed that mastery-approach goals were positively predicted by perceived competence, mastery team climate, learning/enjoyment parental climate, and gender, with males being higher on these goals than females. Mastery-avoidance goals were predicted positively by learning/enjoyment parental climate and negatively by gender, with females being higher on these goals than males. Performance-approach goals were positively predicted by perceived competence, performance team climate, and gender, with males being higher on these goals than females. Finally, performance-avoidance goals were predicted positively by worry-conducive parental climate. These findings suggest that a mastery or performance climate is related to whether athletes adopt a mastery or performance goal, whereas the perception of competence is associated with whether athletes adopt approach-focused goals. Gender should be considered in future examinations of the approach-avoidance achievement goals in sport.